Two-dimensional mathematical model of the dynamic for the fluid and gases (CO2 and O2 ) concentrations in the pulmonary alveolar sacs (Selecciones Matemáticas, 2017)
We simulated the dynamics of CO2 transport in the alveolar sacs of the human lung. Using Arbitrary Lagrangian Eulerian (ALE) framework, we control the movement domain for a normal and fast maneuver. The fluid of room air inspired and CO2 concentrations were approximated by Navier-Stokes and convection diffusion equations; the stress-stretch in the wall for different volumes were quantified in equal time of respiration. The expansion for a normal and forced maneuver were represented as 9 and 90% to the initial geometry. The difference of the CO2 was 73x10
Keywords: Alveolar gas dynamic; Arbitrary Lagrangian-Eulerian; Navier-Stokes equation